The Growth of Tilapia (Oreochromis niloticus) with the Addition of Probiotics to Feed in Sakatiga Village, Indralaya District, Ogan Ilir Regency, South Sumatera - Veronika Oktavia Br Sinaga; Retno Cahya Mukti (Department of Aquaculture, 2022)
Feed is a source of energy to support the growth and survival of fish. To increase feed consumption to the maximum, it is necessary to add an intake to fish feed to increase the digestibility of fish to feed. One alternative that can be done is by adding (supplements) to the feed. Probiotics are an alternative that can be used as a supplement to aquaculture fish feed. The purpose of this field practice is to determine the effect of adding probiotics on the growth of tilapia. This field practice was carried out in August - October 2020 in Sakatiga Village, Indralaya District, Ogan Ilir Regency, South Sumatera. In infield practice, there were two treatments, namely P0: control (without the addition of probiotics) and P1: treatment with the addition of probiotic EM4 at a dose of 15 ml/kg. The container used is a waring placed in a concrete tub. The stages of the implementation of this field practice start from the preparation of containers, adding probiotics to feed, raising tilapia, and collecting data. The parameters observed were fish growth (length and absolute weight), specific growth rate, feed conversion (FCR), fish survival, and water quality (temperature and pH). The results showed that the results of the P1 treatment gave better results than the P0 treatment, the absolute length growth of 3.71 cm, the absolute weight growth of 6.10 g, the specific growth rate of 5.15% / day, the FCR of 0.74, and survival of 90%. The water quality in both treatments during maintenance was included in the normal standard for tilapia as the temperature of 27.5 - 29.8 °C and pH of 6.7 - 8.4. The addition of probiotics can be proposed as an effort to increase the production of tilapia aquaculture.